2015
DOI: 10.1371/journal.pone.0119310
|View full text |Cite
|
Sign up to set email alerts
|

Effects of TiO2 and Co3O4 Nanoparticles on Circulating Angiogenic Cells

Abstract: Background and AimSparse evidence suggests a possible link between exposure to airborne nanoparticles (NPs) and cardiovascular (CV) risk, perhaps through mechanisms involving oxidative stress and inflammation. We assessed the effects of TiO2 and Co3O4 NPs in human circulating angiogenic cells (CACs), which take part in vascular endothelium repair/replacement.MethodsCACs were isolated from healthy donors’ buffy coats after culturing lymphomonocytes on fibronectin-coated dishes in endothelial medium for 7 days. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…To evaluate potential SGLT2i cytotoxic action in MAC, we assessed cell viability by using VisionBlue fluorescence cell viability assay kit (Biovision, Mountain View, CA), following manufacturer's instructions, as already reported [16,21,23]. Briefly, MACs were cultured in 96-well culture plates at a density of 2.5 × 10 5 cells per well (in a volume of 100 µl of culture medium) and exposed to EMPA and DAPA (1, 10 and 100 µM) for 16 h. Ten microliters of VisionBlue reagent was added in each well and, following incubation (2 h at 37 °C), the fluorescent product was measured (excitation: 540 nm, emission: 586 nm) using Cary Eclipse spectrophotometer (Varian/Agilent, Santa Clara, CA, USA).…”
Section: Viability Assay In Macmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate potential SGLT2i cytotoxic action in MAC, we assessed cell viability by using VisionBlue fluorescence cell viability assay kit (Biovision, Mountain View, CA), following manufacturer's instructions, as already reported [16,21,23]. Briefly, MACs were cultured in 96-well culture plates at a density of 2.5 × 10 5 cells per well (in a volume of 100 µl of culture medium) and exposed to EMPA and DAPA (1, 10 and 100 µM) for 16 h. Ten microliters of VisionBlue reagent was added in each well and, following incubation (2 h at 37 °C), the fluorescent product was measured (excitation: 540 nm, emission: 586 nm) using Cary Eclipse spectrophotometer (Varian/Agilent, Santa Clara, CA, USA).…”
Section: Viability Assay In Macmentioning
confidence: 99%
“…cDNA was obtained by iScript Reverse Transcription Kit (Bio-Rad Laboratories, Inc. Hercules, Ca, USA) starting from 250 ng of total RNA. Interleukin (IL)-1β, IL-8, tumor necrosis factor-α (TNF-α), and monocyte chemoattractant protein-1 (MCP-1) gene expression was tested using SsoAdvanced Universal Probes Supermix (Bio-Rad) with TaqMan primers and probes (IL-1β: Hs01555410_m1; IL-8: Hs00174103_m1; TNF-α: Hs00174128_m1; MCP-1: Hs00234140_m1) (Applied Biosystems, Carlsbad, CA, USA) on a CFX Connect Real-Time (Bio-Rad), as previously reported [16,23]. Specific thermal cycling conditions were used: 98 °C for 30 s, followed by 40 amplification cycles (95 °C for 3 s; 60 °C for 20 s).…”
Section: Pro-inflammatory and Oxidant Stress Marker Gene Expression Imentioning
confidence: 99%
“…Examples include cell senescence, cell death, proliferation, growth arrest, autophagy, and adaptation. Human circulating angiogenic cells (CACs) exposed to increasing concentrations (up to 100 µg/mL) of TiO 2 and tricobalt tetraoxide (Co 3 O 4 ) NPs exhibit significant reduction in cell viability, enhanced caspase activity, increased lipid peroxidation end products and upregulation of proinflammatory cytokine gene expression . After treatment by these NPs, CACs in vascular endothelium repair and replacement were subsequently impaired.…”
Section: Metallic and Metallic Oxide Nanoparticle‐induced Oxidative Smentioning
confidence: 99%
“…Similarly, Co 3 O 4 nanoparticles induced apoptosis (at 10-25 µg/mL) in leukemic cancer cells [24]. Spigoni et al [35] reported that Co 3 O 4 nanoparticles significantly reduced cell viability, and induced apoptosis, oxidative stress, caspase activity, and pro-inflammatory cytokine gene expression in vitro. They indicated that the adverse effects might be relevant for a potential role of exposure to titanium dioxide (TiO 2 ) and Co 3 O 4 nanoparticles in enhancing cardiovascular risk in humans.…”
Section: Resultsmentioning
confidence: 97%